Evolutionary game between government and shipping enterprises based on shipping cycle and carbon quota - Xiao, Guangnian; Cui, Wenya (Frontiers in Marine Science, 2023)
With the opening of the national carbon trading market and the coming of the post-epidemic era, the government actively promotes the carbon quota policy to fundamentally achieve carbon emission reduction. This paper corresponds the shipping cycle to the shipping market demand situation during the epidemic, incorporates the shipping cycle characteristics and government quota characteristics into a multi-stage evolutionary game model. Later, the study analyzes the equilibrium points of the game parties at each stage and finally investigates the influence of factors such as technological improvement on the strategy choice of shipping enterprises through sensitivity analysis. The study found that the government’s carbon quota policy is influenced by shipping market demand. During the peak shipping season, the government’s quota policy is binding on shipping enterprises. In the low season of shipping, the binding effect of government’s quota policy on shipping enterprises will be reduced, or even appear to be invalid. Therefore, the government should forecast the demand situation of the shipping market, gradually relax the regulation during the peak season of shipping, and strengthen the regulation before the low season of shipping. Shipping enterprises should increase the research and development of carbon emission reduction technology to reduce carbon emissions from the root to realize the sustainable development of ports and marine-related industries in the post-epidemic era.